BMP Signaling Controls Formation of a Primordial Germ Cell Niche within the Early Genital Ridges - Dudley, Brian (2010)
Stem cells are necessary to maintain tissue homeostasis and the microenvironment (a.k.a. the niche) surrounding these cells controls their ability to self renew or differentiate. For many stem cell populations it remains unclear precisely what cells and signals comprise a niche. Here we identify a possible PGC niche in the mouse genital ridges. Conditional ablation of Bmpr1a was used to demonstrate that BMP signaling is required for PGC survival and migration as these cells colonize the genital ridges. Reduced BMP signaling within the genital ridges led to increased somatic cell death within the mesonephric mesenchyme. Loss of these supporting cells correlated with decreased levels of the mesonephric marker, Pax2, as well as a reduction in genes expressed in the coelomic epithelium including the putative PGC chemo-attractants Kitl and Sdf1a. We propose that BMP signaling promotes mesonephric cell survival within the genital ridges and that these cells support correct development of the coelomic epithelium, the target of PGC migration. Loss of BMP signaling leads to the loss of the PGC target resulting in reduced PGC numbers and disrupted PGC migration.